2017
DOI: 10.21475/ajcs.17.11.12.pne315
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and early development of tomato seedlings cv. santa clara in alternative substrates

Abstract: A quality substrate is essential to ensure the proper conditions for the emergence and early development of seedlings. The aim of the present study was to evaluate different proportions of termite mound substrate in the emergence and early development of tomato seedlings. The experiment was performed in a completely randomized design, with five treatments constituted by the substrates, with four replications: T 1 : Washed sand (100%); T 2 : Washed sand (75%) + termite mound material (25%); T 3 : Washed sand (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
(16 reference statements)
0
3
0
2
Order By: Relevance
“…Fonte: Silva et al (2020) Maior acúmulo de massa da matéria seca da parte aérea (MSPA) em plantas de mostarda foi verificado na dose 72,75 g dm -3 (ẋ = 0,86 g planta -1 ), com incremento de 43,56 % em comparação às plantas testemunhas (ẋ = 0,367 g planta -1 ) (Figura 3A). Estes resultados estão de acordo com as observações de Santos et al (2017) Figura 3. Massa da matéria seca da parte aérea (MSPA) (A), massa da matéria seca da raiz (MSR) (B); massa da matéria total (MST) (C) e relação da massa da matéria seca da raiz e parte aérea (RMSRPA) (D) de plantas de mostarda em função a doses de material de cartão de cupinzeiro.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Fonte: Silva et al (2020) Maior acúmulo de massa da matéria seca da parte aérea (MSPA) em plantas de mostarda foi verificado na dose 72,75 g dm -3 (ẋ = 0,86 g planta -1 ), com incremento de 43,56 % em comparação às plantas testemunhas (ẋ = 0,367 g planta -1 ) (Figura 3A). Estes resultados estão de acordo com as observações de Santos et al (2017) Figura 3. Massa da matéria seca da parte aérea (MSPA) (A), massa da matéria seca da raiz (MSR) (B); massa da matéria total (MST) (C) e relação da massa da matéria seca da raiz e parte aérea (RMSRPA) (D) de plantas de mostarda em função a doses de material de cartão de cupinzeiro.…”
Section: Resultsunclassified
“…Apesar desses atributos químicos, escassas são as pesquisas sobre o uso do MCC como adubo orgânico, em pesquisas já realizadas foram verificados efeitos significativos no rendimento da alface (INOCÊNCIO et al, 2009), maracujá (SOUSA et al, 2011) e tomate (SANTOS et al, 2017), entretanto para a cultura da mostarda ainda não há estudos utilizando esse adubo orgânico.…”
Section: Introductionunclassified
“…In order to achieve unbroken test for pepper plug seedlings, a calculating model based on leaf area image parameters showed that the determination coefficient of pepper leaf area and plant dry weight was 0.9312, which reached a significant level of correlation [8]. Through experimental researches, different proportions were evaluated of termite mound substrate in the emergence and early development of tomato seedlings, were emergence, emergence speed index, shoot height, number of leaves, shoot dry mass, root length and root dry mass of tomato seedling development were evaluated after 25 days [9].…”
Section: Introductionmentioning
confidence: 99%
“…Zuffo et al | Substrates for the production of lettuce seedlings mound material have been reported for lettuce (Inocêncio et al, 2009), maroon cucumber (Cucumis anguria L.) (Cardoso et al, 2013) and tomato (Solanum lycopersicum L.) (Santos et al, 2017). However, studies using substrates formulated from mixtures of termite mound with bees' nest materials are scarce and unknown.…”
mentioning
confidence: 99%
“…However, studies using substrates formulated from mixtures of termite mound with bees' nest materials are scarce and unknown. Thus, the search for alternative materials for the formulation of substrates has become the goal of many researches, mainly to reduce the use of industrialized inputs, which promoting sustainable agricultural systems (Oliveira, 2011;Santos et al, 2017).…”
mentioning
confidence: 99%